Interleukin-33 exerts pleiotropic immunoregulatory effects in response to Plasmodium berghei ANKA (PbA) infection in mice - Abd Rachman Isnadi, Mohammad Faruq; Basir, Rusliza; Omenesa, Ramatu Bello; Abd Majid, Roslaini; Abdullah, Maizaton Atmadini; Mat Taib, Che Norma; Priya, Sivan Padma; Kong, Yong Yean; Kin, Chin Voon; Mukhtar, Gambo Lawal (Wolters Kluwer Medknow Publications, 2023)
Objective: To determine the involvement and the modulatory effects of IL-33 during Plasmodium berghei ANKA (PbA) infection. Methods: PbA infection in male ICR mice was utilized as a model of malaria. Systemically circulating IL-33 levels were determined in blood plasma by enzyme-linked immunosorbent assay (ELISA). After 24 hours post-inoculation of PbA, recombinant IL-33 and ST2, and antibodies against IL-33 and IgG treatments were administered daily for 3 days. Tissue expression and localization of IL-33 were assessed in organs generally affected by malaria via immunohistochemistry. Moreover, histopathological examination was performed to assess the effects of the treatments. Results: The levels of systemic IL-33 were elevated at the critical phase of PbA infection. Likewise, immunohistochemical analysis revealed a significant upregulation of IL-33 expression at the critical phase in the brain, lungs, and spleen of PbA-infected mice as compared to healthy controls. Treatment with IL-33 protected against experimental cerebral malaria development and reduced pathological features in the brain and lungs of the PbA-infected mice. Conclusions: A potential critical role and involvement of IL-33 in PbA infection may hint at the resolution of immunopathological sequelae associated with malaria.